Quality of Life of Permanent Workers of a Cement Factory in Bangladesh (Jalalabad Medical Journal, 2026)
Cement factory workers are exposed to dust, fumes and gases that cause various health-related issues in different systems. All work-related negativities consist of a risk for one’s health that affects an individual’s quality of life (QOL) in the short and long run. This study aimed to evaluate the quality of life of permanent workers in a cement factory in Bangladesh. This cross-sectional study was conducted on permanent workers aged between 18 to 60 years from Lafarge Holcim Bangladesh Ltd, Chatak. The WHOQOL-BREF scale was used to assess QOL. There was a total of 131 of 150 (87.3%) cement factory workers solemnly enrolled in this study. The mean age was 30.39±6.4 years. Among all study participants, 38.3% had been working for less than 5 years, 30.5% had been working between 5 to 9 years, 27.5% for 10-14 years, and the rest 3.1% for ≥15 years. Mean general QOL score was 61.22±9.84 and the mean general health score was 72.36±10.94. Among all four domains of QOL, the socioeconomic domain (66.11±11.52) had the highest score, followed by psychological health (59.97±6.59), environmental health (57.93±7.50) and physical health (56.27±5.99). Based on this cross-sectional study, it can be concluded that the cement factory workers were largely satisfied with their quality of life.Jalalabad Med J 2025; 22 (1): 12-16.